2012
DOI: 10.1261/rna.027698.111
|View full text |Cite
|
Sign up to set email alerts
|

A 5′-terminal phosphate is required for stable ternary complex formation and translation of leaderless mRNA in Escherichia coli

Abstract: The bacteriophage l's cI mRNA was utilized to examine the importance of the 59-terminal phosphate on expression of leadered and leaderless mRNA in Escherichia coli. A hammerhead ribozyme was used to produce leadered and leaderless mRNAs, in vivo and in vitro, that contain a 59-hydroxyl. Although these mRNAs may not occur naturally in the bacterial cell, they allow for the study of the importance of the 59-phosphorylation state in ribosome binding and translation of leadered and leaderless mRNAs. Analyses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…40,62 Indeed, strand specific sequencing and TSS mapping of the archea Sulfolobus solfataricus showed that most transcripts completely lack 5' UTR sequences. For 69% of the protein coding transcripts the transcription began exactly at the "A" of the AUG translational start site or 1-3 bases upstream of the AUG. 43 Giliberti and colleagues 63 showed that the 5'-terminal phosphate is important for ribosome binding to allow translation initiation also from leaderless mRNAs in contrast to leadered mRNAs that are well expressed with either a 5'terminal phosphate or hydroxyl. It will be interesting to analyze whether this is also the case for leaderless transcripts in L. pneumophila and for those leaderless mRNAs where the CDS does not start with AUG.…”
Section: Resultsmentioning
confidence: 99%
“…40,62 Indeed, strand specific sequencing and TSS mapping of the archea Sulfolobus solfataricus showed that most transcripts completely lack 5' UTR sequences. For 69% of the protein coding transcripts the transcription began exactly at the "A" of the AUG translational start site or 1-3 bases upstream of the AUG. 43 Giliberti and colleagues 63 showed that the 5'-terminal phosphate is important for ribosome binding to allow translation initiation also from leaderless mRNAs in contrast to leadered mRNAs that are well expressed with either a 5'terminal phosphate or hydroxyl. It will be interesting to analyze whether this is also the case for leaderless transcripts in L. pneumophila and for those leaderless mRNAs where the CDS does not start with AUG.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, a large number of bacterial genes, including genes that are expressed at high level, do not have a 5′ UTR or have just a few bases upstream the coding sequence that begins with a 5′ AUG [ 36 ]. Translation of these leaderless mRNAs likely involves an ancestral mechanism, conserved in bacteria, archaea and eukaryotic cells [ 36 , 37 ] and depends on IF2 [ 36 , 38 ], on 5′ phosphorylated AUG [ 12 , 39 , 40 ] and is antagonized by IF3 [ 41 ]. It has also been suggested that translation of these mRNAs begins with 70S monomers instead of 30S subunits [ 42 44 ].…”
Section: Properties Of the Mrna Translation Initiation Regions (Tirs)mentioning
confidence: 99%
“…Pairing between the SD sequence and anti-SD (aSD) sequence on the small subunit ribosomal RNA is important for start codon localization ( Hui & de Boer, 1987 ; Vimberg et al , 2007 ), although such pairing is not always essential in translating E. coli messages ( Fargo et al , 1998 ; Melançon et al , 1990 ) or in Chlamydomonas reinhardtii chloroplasts ( Fargo et al , 1998 ). Some leaderless genes with an AUG start codon can be translated efficiently in E. coli ( Giliberti et al , 2012 ; Krishnan et al , 2010 ; O’Donnell & Janssen, 2002 ; Vesper et al , 2011 ) or in the halophilic archaeon Halobacterium salinarum ( Sartorius-Neef & Pfeifer, 2004 ). However, translation initiation of most E. coli genes appears to benefit from a well-positioned SD sequence, especially genes that follow the first gene in a multigene operon ( Osterman et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%